Personalizing Auditory Training: Understanding Individual Factors in Adult Cochlear Implant Users - Tamati, Terrin N.; Saraino, Michayla M.; Birenbaum, Sarah M.; Moberly, Aaron C. (Seminars in Hearing, 2025)
Cochlear implants (CIs) are an incredibly effective surgical intervention for many adults with moderate-to-profound sensorineural hearing loss and ideally improve communication ability and quality of life. However, although CIs restore sound access, they do not guarantee real-world speech communication abilities. To optimize communication outcomes, CI users have access to numerous auditory training (AT) approaches, including patient-directed and clinician-guided interventions. Despite the widespread use of AT, research on its benefits in adult CI users remains limited, resulting in a critical gap in understanding the individual factors that drive variability in training outcomes among adult CI users. This review paper synthesizes evidence on demographic, auditory, cognitive-linguistic, and psychosocial factors that influence responsiveness to AT. Given the well-documented influence of these factors on speech perception outcomes in adult CI users, we propose that a set of shared or unique factors likely predict CI users' responses to AT interventions. By understanding individual differences, future AT interventions can be better tailored to the needs of each CI user, moving beyond a one-size-fits-all model. In addition, we discuss the need to broaden our outcome assessments of AT beyond traditional speech recognition measures to real-world speech communicative and social functioning, which are likely to impact hearing-related and overall quality of life in this patient population. These insights provide a foundation for more effective, personalized AT strategies that address the diverse needs of adult CI users.
Keywords: cochlear implants; auditory training; individual differences; cognition; speech perception